From Makhaza to Rammulotsi : reflections on South Africa's "toilet election" of 2011 (Historia, 2021)
In the run-up to South Africa's 2011 local election, the event was labelled the "toilet election" in the media. The message that struck a sensitive chord in the national newspapers was that some local authorities were not compliant in terms of water and sanitation service delivery. Service delivery, in itself, had been a crucial issue in municipal politics since the previous local election of 2006. Four years later, as local politicians prepared for the 2011 countrywide municipal election, the townships of Makhaza in Cape Town and the rural Rammulotsi near the Free State town of Viljoenskroon, were in the news. There was a pubic outcry because of the undignified manner in which local residents had to use the outdoor toilets that were not properly enclosed. From time to time news reports on the open toilets provided moments of comic relief in a tense election campaign that saw the two leading political parties of the country, the African National Congress and the Democratic Alliance, wooing the electorate. The outspoken public disdain over highly unsatisfactory sanitation services, underlined the need for politicians and the management of local authorities to pay serious attention to efficient governance at the municipal level in a democratic society. In the article dedicated attention is also given to the way in which the local election influenced water and sanitation service delivery planning in Moqhaka Local Municipality, the local authority that oversees Rammulotsi township.  In die tydperk wat die plaaslike verkiesing van 2011 in Suid-Afrika voorafgegaan het, is die benaming van die "toiletverkiesing" aan die gebeurtenis gekoppel. Die boodskap, wat 'n sensitiewe snaar in die nasionale nuusmedia aangeraak het, was die feit dat daar plaaslike owerhede was wat nie in ooreenstemming met aanvaarde praktyke hul verantwoordelikhede ten opsigte van diens lewering nagekom het nie. Dienslewering opsigself was sedert die vorige plaaslike verkiesing van 2006 'n kritieke gesprekspunt. Vier jaar later, terwyl politici hulle vir die volgende verkiesing voorberei het, het Makhaza in Kaapstad en Rammulotsi, naby Viljoenskroon in die Vrystaatprovinsie, in die nuus opslae gemaak. Daar was duidelike openbare ontevredenheid met die onmenswaardige wyse waarop plaaslike inwoners behandel is deurdat hulle spoeltoilette sonder behoorlike afskortings moes gebruik. Nuus omtrent die toilette het van tyd tot tyd vir komiese verligting gesorg in 'n verkiesingstryd wat deur hoë vlakke van openbare spanning gekenmerk is as gevolg van die intense veldtogte van die regerende African National Congress (ANC) and die Demokratiese Alliansie (DA). In die artikel word in die besonder ook aandag gegee aan die wyse waarop die verkiesing beplanning rondom water en sanitasiedienslewering geraak het in Moqhaka Plaaslike Munisipaliteit, waarin Rammulotsi geleë is.
Keywords: Plaaslike owerhede; Plaaslikeverkiesings; Makhaza (Cape Town); Local elections; Water- en sanitasiesektor; Civil society; Water and sanitation sector; Rammulotsi (Viljoenskroon); African National Congress; Local government; Burgerlikesamelewing; Demokratiese Alliansie (DA); Toiletverkiesing 2011; Service delivery; Makhaza (Kaapstad); Dienslewering; Toilet election, 2011; Democratic Alliance